Changing the Reactivity of Zero- and Mono-Valent Germanium with a Redox Non-Innocent Bis(silylenyl)carborane Ligand - Yao, Shenglai; Kostenko, Arseni; Xiong, Yun; Lorent, Christian; Ruzicka, Ales; Driess, Matthias (Angewandte Chemie (International ed. in English), 2021)
Using the chelating C,C'-bis(silylenyl)-ortho-dicarborane ligand, 1,2-(RSi)2 -1,2-C2 B10 H10 [R=PhC(NtBu)2 ], leads to the monoatomic zero-valent Ge complex ("germylone") 3. The redox non-innocent character of the carborane scaffold has a drastic influence on the reactivity of 3 towards reductants and oxidants. Reduction of 3 with one molar equivalent of potassium naphthalenide (KC10 H8 ) causes facile oxidation of Ge0 to GeI along with a two-electron reduction of the C2 B10 cluster core and subsequent GeI -GeI coupling to form the dianionic bis(silylene)-supported Ge2 complex 4. In contrast, oxidation of 3 with one molar equivalent of [Cp2 Fe][B{C6 H3 (CF3 )2 }4 ] as a one-electron oxidant furnishes the dicationic bis(silylene)-supported Ge2 complex 5. The Ge0 atom in 3 acts as donor towards GeCl2 to form the trinuclear mixed-valent Ge0 →GeII ←Ge0 complex 6, from which dechlorination with KC10 H8 affords the neutral Ge2 complex 7 as a diradical species.
Keywords: carboranes; redox non-innocent ligands; germanium; tetrylones; germylone